Lantana camara: Phytochemical Analysis and Antifungal Prospective - BASHIR,S. (2019)
ABSTRACT: In the current study phytochemical analysis and in vitro antifungal potential of fruits, leaves and stem of Lantana camara L. were studied. The phytochemical analysis indicated the presence of alkaloids, flavonoids, tannins, saponins, glycosides and terpenoids in fruit, stem and leaves of L. camara. The in vitro antifungal activity of fruit, stem and leaves of L. camara was tested against Colletotrichum gloeosporioides Penz. Different concentrations (1-5%) of methanolic extract of all the selected parts of L. camara were applied in vitro against the test fungus. The results of in vitro experiment revealed that higher concentration of methanolic fruit extract (5%) significantly reduced the biomass C. gloeosporioides up to 66%. This effective extract of L. camara was partitioned with n-hexane, chloroform, ethyl acetate and n-butanol. The bioactivity of these fractions was tested against C. gloeosporioides. The trials showed that 0.5% concentration of n-hexane fraction of methanolic fruit extract caused the highest reduction (45%) in the radial colony growth of the test fungus. This effective n-hexane fraction was selected for GC-MS analysis to identify various possible antifungal compounds. Cyclopropane, carboxylic acid, 5-heptonic acid, 2,2-dimethyl1-4-pentenoate and 2-Propyloctahydro-1-benzothiophene were identified as major compounds. This study can be concluded that L. camara fruit comprised of bioactive compounds which possess antifungal activity against C. gloeosporioides.